Insights into Resistance to Fe Deficiency Stress from a Comparative Study of In Vitro-Selected Novel Fe-Efficient and Fe-Inefficient Potato Plants - Boamponsem, Georgina A.; Leung, David W. M.; Lister, Carolyn (Frontiers in Plant Science, 2017)
Iron (Fe) deficiency induces chlorosis (IDC) in plants and can result in reduced plant productivity. Therefore, development of Fe-efficient plants is of great interest. To gain a better understanding of the physiology of Fe-efficient plants, putative novel plant variants were regenerated from potato (Solanum tubersosum L. var. ‘Iwa’) callus cultures selected under Fe deficient or low Fe supply (0-5 µM Fe). Based on visual chlorosis rating (VCR), 23% of callus-derived regenerants were classified as Fe-efficient (EF) and 77% as Fe-inefficient (IFN) plant lines when they were grown under Fe deficiency conditions. Stem height was found to be highly correlated with internodal distance, leaf and root lengths in the EF plant lines grown under Fe deficiency conditions. In addition, compared to the IFN plant lines and control parental biotype, the EF plants including the lines named A1, B2 and B9, exhibited enhanced formation of lateral roots and root hairs as well as increased expression of ferritin (fer3) in the leaf and iron-regulated transporter (irt1) in the root. These morphological adaptations and changes in expression the fer3 and irt1 genes of the selected EF potato lines suggest that they are associated with resistance to low Fe supply stress.